(untitled) (Albayan Scientific Journal, 2023)
Arum cyreniacum herbs are distributed close to agricultural crops, especially in AlJabal Al-Akhdar region. therefore, this study aimed of testing an allelopathic effect of aqueous extracts of (leaves and tubers) of Arum cyreniacum at a concentration (10, 20 and 40%) on germination of seeds of some leguminous crop’s plants (Lens culinaris, Cicer arietinum, and Lupinus albus). The results showed that there were highly significant differences in germination percentage reduction between aqueous extracts and concentrations compared with control. Where extracts of leaves were superior in recording the largest inhibition ratios compared to tubers extract, as all tested concentrations significantly decreased germination percentage except for a concentration of 10% for Lens culinaris and Cicer arietinum plants with germination percentage (100%), with a delay an average time of germination, and was a concentration of 40% is the most toxic in inhibiting the growth of all seeds tested. ​The results also noted that all extracts with their concentration led to a reduction in radical and plumule length of all seeds tested.Lens culinaris, Cicer arietinum were the most leguminous types resistant of aqueous extracts, while Lupinus albus were the most sensitive.